Persebaran Kebudayaan dan Peninggalan Sejarah Suku Melayu di Kawasan Medan Maimun : (Studi Pelestarian Identitas Budaya Lokal) - Habibatul Qolbi Sumardi; Ruth Sahana Manalu; Asima Tiara Agnesia Pasaribu; Yogi Marselinus Turnip (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2025)
The purpose of this study is to analyze the distribution and condition of historical heritage, which symbolizes the identity of Malay culture in the Medan Maimun area. This study uses a case study approach for its qualitative method. Information is obtained through direct observation at the location, intensive interviews with local residents and site managers, and review of historical archive documents. The findings show that although the Maimun Palace, the Grand Mosque, and Sri Deli Park have a high level of culture, there are elements of modernization, lack of structural problems, and inadequate maintenance, which cause great difficulties in preserving these heritages. Therefore, there is a need for the government, community, and academics to work together in determining the best conservation strategy.